TRADISI BERARAK TEPIAN DALAM UPACARA PERNIKAHAN DI DESA BULUH NIPIS KECAMATAN SIAK HULU KABUPATEN KAMPAR - Katrin, Yosdalifa; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Indonesia is an anthropological country of 500 ethnic group language and culture features. Even more unique, earch of ethnic group has its own country of origin, historical experience and ancestry. In the countryside generates a variety of tradition that are very important and meaningful, but the villagers take the tradition as a regular thing that they routinely do and become something very valuable, unique and very interesting as important and sacred. The purpose of study is (1) To know the tradition history of lonely rhythmic in the wedding ceremony at the village of Buluh Nipis Siak Hulu Kampar District, (2) To find out the procedures of the tradition of parade in the wedding ceremony in the village of Buluh Nipis Siak Hulu Kampar District, (3) To know the values contained in the implementation of tradition a long the parade of wedding ceremony in the village of Buluh Nipis Siak Hulu Kampar District, (4) To know conservation effort the tradition of parade in the wedding ceremony in the village of Buluh Nipis Siak Hulu Kampar District. The method used in this research is the historical method. The result of this research is the tradition parade to ledges that tradition has long been in the village of Buluh Nipis in a wedding that started with negotiation and the beginning of the feast. The opening wedding ceremony marked by beating of talempong by ninik mamak and short speech, tradition parade to ledges becomes very important because it is a sign of respect and glory for the bride.Keyword: Tradition, Parade to Ledges, Wedding